2018
DOI: 10.2147/ott.s177252
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of APC11 predicts worse survival in lung adenocarcinoma

Abstract: BackgroundAnaphase-promoting complex subunit 11 (APC11) plays an important role in gathering E2 and catalyzing ubiquitin-chain formation to support ubiquitination of substrates by acting as a catalytic core subunit of anaphase-promoting complex (APC/C). However, whether APC11 is implicated in the tumorigenesis of lung cancer is never known.Materials and methodsIn this study, we used an online survival analysis software to estimate the prognostic value of APC11 mRNA expression level for lung cancer. Cell Counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Conversely, APC11 overexpression promoted cell proliferation and was associated with poorer prognosis. Collectively these findings show that APC11 crucially contributes to the development of lung adenocarcinoma (Zhou et al 2018). APC11 overexpression has also been reported in colorectal cancer cell lines, which significantly correlated with chromosomal instability, lymphovascular invasion and residual tumours (Drouet et al 2018).…”
Section: Apc/c Deregulation Drives Carcinogenesismentioning
confidence: 78%
See 1 more Smart Citation
“…Conversely, APC11 overexpression promoted cell proliferation and was associated with poorer prognosis. Collectively these findings show that APC11 crucially contributes to the development of lung adenocarcinoma (Zhou et al 2018). APC11 overexpression has also been reported in colorectal cancer cell lines, which significantly correlated with chromosomal instability, lymphovascular invasion and residual tumours (Drouet et al 2018).…”
Section: Apc/c Deregulation Drives Carcinogenesismentioning
confidence: 78%
“…Abnormally high expression levels of APC11 have been reported in lung cancer (Zhou et al 2018) where high APC11 messenger RNA (mRNA) levels significantly correlated with poorer overall survival for lung adenocarcinoma. siRNA knockdown of APC11 arrested cells in mitosis and significantly reduced cell proliferation, colony formation and migration and invasive capabilities.…”
Section: Apc/c Deregulation Drives Carcinogenesismentioning
confidence: 99%
“…This balance may explain why only a fraction of cells overexpressing Apc11 cleaved Scc1. Nevertheless, the dire physiologic consequences of unregulated Apc11 are evident from 2 very recent studies that identified physiologic excess of Apc11 in colorectal cancer (44) and adenocarcinoma (45). In the first manuscript, different mRNA and protein expression analyses [quantitative real-time-PCR, Western blot, Tissue MicroArray (TMA) of 82 primary colorectal cancer tissues, and public datasets], revealed that the overexpression of APC11, but not of other APC/C subunits (APC2 and APC10), is significantly correlated with chromosomal instability.…”
Section: Discussionmentioning
confidence: 99%